Design kolébkové pily - Ferda, Tomáš (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2019)
Tématem diplomové práce je návrh designu kolébkové pily. Náplň práce se zabývá popisem nedostatků současných řešení, z kterých vyvozuje závěry. Cílem je tedy snaha o vyvarování se zjištěným problémům a vylepšení tak kolébkové pily především po vizuální a ergonomické stránce.

This thesis describes a proposal for a rocker saw design. It addresses the general lack of current solutions, their description and it is drawing conclusions of these. The object of this thesis is to try to avoid potential problems which are being discussed in this thesis and therefore suggests solutions for enhancing the rocker saw, especially on the visual and ergonomic side.
Design of Firewood Saw
Keywords: Design; kolébková pila; okružní pila; ergonomie; bezpečnost; Design; rocker saw; circular saw; ergonomics; safety